2016
DOI: 10.1371/journal.pone.0154011
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Dilation and Pulmonary Vasodilatation after Surgical Shunt for Treatment of Pre-Sinusoidal Portal Hypertension

Abstract: ObjectiveThe aim of this study was to prospectively investigate the long-term cardiovascular and pulmonary hemodynamic effects of surgical shunt for treatment of portal hypertension (PH) due to Schistosomiasis mansoni.LocationThe University of São Paulo Medical School, Brazil; Public Practice.MethodsHemodynamic evaluation was performed with transesophageal Doppler and contrast-enhanced echocardiography (ECHO) on twenty-eight participants with schistosomal portal hypertension. Participants were divided into two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…It was demonstrated that pulmonary artery enlargement is more pronounced in schistosomiasis-induced PAH than an- other form of PAH, suggesting that this is a more distinct feature of schistosomiasis-induced PAH (Figure 3). [43][44][45] Electrocardiography may show right ventricular hypertrophy or strain and right atrial enlargement, and may also reveal a right bundle branch block. Echocardiography may demonstrate right ventricular dilatation, potentially compressing the left ventricle with septal bowing, usually accompanied by right atrial dilation, tricuspid valve regurgitation, and an increased pressure gradient across the tricuspid valve as well as dilatation of the main pulmonary artery.…”
Section: Clinical Presentation Of Schistosomiasis-induced Pahmentioning
confidence: 99%
“…It was demonstrated that pulmonary artery enlargement is more pronounced in schistosomiasis-induced PAH than an- other form of PAH, suggesting that this is a more distinct feature of schistosomiasis-induced PAH (Figure 3). [43][44][45] Electrocardiography may show right ventricular hypertrophy or strain and right atrial enlargement, and may also reveal a right bundle branch block. Echocardiography may demonstrate right ventricular dilatation, potentially compressing the left ventricle with septal bowing, usually accompanied by right atrial dilation, tricuspid valve regurgitation, and an increased pressure gradient across the tricuspid valve as well as dilatation of the main pulmonary artery.…”
Section: Clinical Presentation Of Schistosomiasis-induced Pahmentioning
confidence: 99%